2009
DOI: 10.1007/s11033-009-9654-8
|View full text |Cite
|
Sign up to set email alerts
|

A new SNP in the 3′UTR region of the bovine calpain small subunit (CAPNS1) gene

Abstract: Calpains are a ubiquitous cytoplasmic cysteine protease, the activity of which is absolutely dependent on calcium. This proteolytic system degrades myofibrillar protein under post-mortem conditions and appears to be the primary enzyme in the postmortem tenderization process. In the present study a new single nucleotide polymorphism was found in the bovine CAPNS1 gene exon 11 coding for the 3'UTR. Transition C --> T at position 6536 was detected and identified using PCR-SSCP and DNA sequencing techniques, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…These authors showed that nearly half of the animals under investigation were heterozygous at the analysed locus. Other studies support the high frequency of the CT genotype (0.58) within Holstein-Friesian cattle [6]. The same tests carried out for meat-producing breeds showed that the CT genotype was also most frequent-it was identified in about 56% of animals of the Limousine breed and 65% of animals of the Charolaise breed.…”
Section: Itemsupporting
confidence: 52%
See 1 more Smart Citation
“…These authors showed that nearly half of the animals under investigation were heterozygous at the analysed locus. Other studies support the high frequency of the CT genotype (0.58) within Holstein-Friesian cattle [6]. The same tests carried out for meat-producing breeds showed that the CT genotype was also most frequent-it was identified in about 56% of animals of the Limousine breed and 65% of animals of the Charolaise breed.…”
Section: Itemsupporting
confidence: 52%
“…So far, however, few studies in this area concerned cattle reared in Poland, including the Holstein-Friesian breed. Moreover, not all of the studies have included an analysis of significant parameters which are of relevance to the quality of beef [6].…”
Section: Introduction mentioning
confidence: 99%
“…CAPN1S gene polymorphism identification of bovine muscles was performed with the assistance of the PCR-RFLP technique employing Mbo II endonuclease [10]. Primers with CAPN1S-F 5′-CCTCACTGTCTGTCCCTTCC-3′ and CAPN1S-R 5′-ACACAAATGTTGGGCTTGG-3′ sequences amplifying 332 bp were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…a regulatory subunit of m-calpain with the above-mentioned traits (meat and fat content in valuable cuts, tenderness, colour, taste, consistence, pH). Recently, polymorphism of a new SNP in the 30UTR region of the bovine μ-calpain small subunit ( CAPNS1 ) gene (exon 11—RFLP/ Mbo II) has been discovered [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, 3 0 UTRs are rich in cis-acting regulatory elements [24]. Juszczuk-Kubiak et al [25] showed that the SNP in the 3 0 UTR of the bovine calpain small subunit gene was associated with meat quality. The mutations g.14248 T > C and g.14391 C> T may affect gene regulation and selective splicing regulation, although g.14248 T > C will not affect the amino acid sequence [26], and subsequently affect the serum concentration and activity of MASP2.…”
Section: Relationship Of Genotypes and Haplotypes Of Masp2 With Milk mentioning
confidence: 99%